ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DALAM BURSA EFEK INDONESIA TAHUN 2015-2017 - Annisa Nugraheni; Bambang Mursito; Sudarwati Sudarwati (ITB AAS INDONESIA Surakarta, 2019)
The purpose of this study was to analyze and assess the financial performance of telecommunication companies listed on the Stock Exchange in 2015-2017 based on financial ratio analysis consisting of: liquidity ratios, solvability ratios, activity ratios and profitability ratios. This type of research is descriptive. Data analysis techniques used are financial ratios with time series calculations and cross sections. The research results based on overall financial ratios show that PT Telekomunikasi Indonesia has the best financial performance compared to other similar companies. Keywords : Financial Performance, Liquidity Ratio, Solvability Ratio, Activity Ratio, Profitability Ratio